PENGARUH KONSENTRASI BUBUR BUAH PISANG TONGKA LANGIT (Musa troglodytarum) DAN CARBOXYL METHYL CELULOSE TERHADAP SIFAT KIMIA DAN ORGANOLEPTIK SORBET AIR KELAPA - Gelora H Augustyn; Dian Rumalean (AGRITEKNO: Jurnal Teknologi Pertanian, 2016)
This study has an objective to determine the influence the concentration of tongka langit banana fruit pulp and CMC on the coconut water sorbet that was produced. This research used factorial completely randomized design (CRD) with two factors consisting of the concentration of banana fruit pulp 50 g, 100 g, 150 g and the concentration of CMC 0 g, 0,5 g, 0,75 g, 1 g. The data were statistically tested using analysis of variance according to the design used, followed by test of honestly significant difference (HSD). The results indicated that the concentration of tongka langit banana fruit 150 g and CMC 1 g produced a good coconut water sorbet, with vitamin C 0.018%, total acids 1.64%, and total sugar 18.1%. Organoleptic values of the attribute value of taste 3.53 and color 4.03.